PENGGUNAAN MEDIA GAMBAR BERSERI UNTUK MENINGKATKAN KEMAMPUAN MENULIS KARANGAN DESKRIPSI MAHASISWA ANGKATAN 2018 PROGRAM STUDI PENDIDIKAN BAHASA JEPANG FKIP UNIVERSITAS RIAU (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The main objective of learning Japanese is to improve students' ability to communicate in Japanese, both spoken and written. Writing ability is a person's ability to describe language with graphic symbols that can be understood by someone easily and clearly. Serial image media is included in the visual form of media. This media is also called a flow chart or stacking images or a collection of images that are different from one another but are sequentially and related to each other. Picture series media are tips that can help students to come up with and develop main ideas in writing descriptive essays. Descriptive essays have the characteristics of describing objects in more detail, using sentences that describe objects and forming the reader's imagination, using figurative words to enrich the picture, emphasizing on five-sense responses, using clear vocabulary, applying one of the organizing patterns, and inserting impressions and fixed atmosphere. The purpose of this paper is to look at the writing skills (sakubun) of students and to find out whether there is an increase in the ability to write descriptive essays for the 2018 students of the Japanese Language Education Study Program FKIP Riau University by using quasi-experimental research (quasi-experimental) with STAD (Student Team Achievement technique Division). The research pattern uses the one group pretest-posttest design method with 20 students as the research subject. From the results of this study, it was found that there was a significant difference between the pre-test and post-test data from the use of serial picture media on learning to write (sakubun), and this is can be concluded that this study was quite satisfactory.Key Words: Descriptive Writing Essay Skills, Picture Series Media, Quasi Experiment.